Comparison of pre-treatment with OCPs or estradiol valerate vs. no pre-treatment prior to GnRH antagonist used for IVF cycles: An RCT - Ensieh Shahrokh Tehrani Nejad; Fatemeh Bakhtiari Ghaleh; Bita Eslami; Fedyeh Haghollahi; Maryam Bagheri; Masoumeh Masoumi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Both oral contraceptive pills (OCPs) and estradiol valerate (E2) have been used to schedule a gonadotropin-releasing hormone antagonist in vitro fertilization (IVF) cycles. Since the suppression of follicle-stimulating hormone by OCPs can stay 5-7 days after stopping the pills, it seems that starting the gonadotropin-releasing hormone (GnRH) after 6 days of pre-treatment discontinuation may be important in IVF outcomes. Objective: The aim of the present study was to determine the number of mature oocyte and pregnancy rate of three pretreatment methods for fresh embryo transfer cycles. Materials and Methods: In this randomized controlled trial, two-hundred ten women (18-35 yr and less than 2 previous IVF attempts) undergoing IVF with the GnRH antagonist protocol were randomized to the OCP, E2, and no pretreatment arms. OCP group (n=53) received OCP (ethinyl estradiol30 μg and levonorgestrel150 μg), E2 group (n=63) received 4 mg/day oral E2 (17β‐E2) for 10 days from day 20 of the previous cycle and GnRH antagonist stimulation was started 6 days after the interruption of OCP and E2. The control group (n =70) did not receive any pretreatment. Results: No significant difference was observed in the mean number of the mature oocyte, endometrial thickness, and embryo quality. The pregnancy rate in E2 group was higher than the two other groups (42.9% vs 39.6% and 34.3% in OCP and control group, respectively), but the difference was not statistically significant (p=0.59). Conclusion: It seems OCP or E2 pretreatment could not improve the fresh IVF-embryo transfer outcomes